2016
DOI: 10.1051/0004-6361/201527066
|View full text |Cite
|
Sign up to set email alerts
|

Starburst galaxies in the COSMOS field: clumpy star-formation at redshift 0 <z< 0.5

Abstract: Context. At high redshift, starburst galaxies present irregular morphologies with 10−20% of their star formation occurring in giant clumps. These clumpy galaxies are considered the progenitors of local disk galaxies. To understand the properties of starbursts at intermediate and low redshift, it is fundamental to track their evolution and the possible link with the systems at higher z. Aims. We present an extensive, systematic, and multiband search and analysis of the starburst galaxies at redshift (0 < z < 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 81 publications
3
19
1
Order By: Relevance
“…The typical size of these objects is ∼ 0.4 arcsec, which is consistent with typical sizes of high-z galaxies as found by (Bouwens et al 2004;Oesch et al 2010;Ono et al 2013;Shibuya et al 2015;Holwerda et al 2015;Liu et al 2017). Moreover, luminous clumps in clumpy galaxies are usually surrounded by a common isophote, embedding the entire galaxy, below the bright level of the clumps but above the background sky (see Hinojosa-Goñi et al 2016). This effect is not seen in our objects.…”
Section: Pair Groups and Overdensitiessupporting
confidence: 85%
“…The typical size of these objects is ∼ 0.4 arcsec, which is consistent with typical sizes of high-z galaxies as found by (Bouwens et al 2004;Oesch et al 2010;Ono et al 2013;Shibuya et al 2015;Holwerda et al 2015;Liu et al 2017). Moreover, luminous clumps in clumpy galaxies are usually surrounded by a common isophote, embedding the entire galaxy, below the bright level of the clumps but above the background sky (see Hinojosa-Goñi et al 2016). This effect is not seen in our objects.…”
Section: Pair Groups and Overdensitiessupporting
confidence: 85%
“…Such an increase may indicate the collision of the starburst gas with the ISM of the host galaxy, as if the star-forming regions were inspiraling towards the galaxy center. This migration to the galaxy center is expected from tidal forces acting upon massive gas clumps (see, e.g., Elmegreen et al 2008;Ceverino et al 2016;Hinojosa-Goñi et al 2016); the large starbursts in our XMPs may be going through such a process at this moment.…”
Section: Mass Of the Central Objectmentioning
confidence: 92%
“…High-resolution imaging has shown that kiloparsec-sized clumps appear to be a common feature of galaxies at intermediate redshifts, and simulations indicate that they form in situ by gravitational instabilities in gas-rich galaxies (Noguchi 1999; Conselice et al 2004;Elmegreen et al 2004;Elmegreen & Elmegreen 2005;Papovich et al 2005;Bournaud et al 2007;Agertz et al 2009;Ceverino et al 2010Hinojosa-Goñi et al 2016. Clumps atz 2 can reach 10 9  M (Guo et al 2012;Tacconi et al 2013); however, their eventual fate remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Clumps atz 2 can reach 10 9  M (Guo et al 2012;Tacconi et al 2013); however, their eventual fate remains uncertain. If they are long-lived (with lifetimes comparable to the orbital timescale of the disk), clumps can migrate inward and provide a path toward bulge growth (Bournaud et al 2007;Ceverino et al 2010;Hinojosa-Goñi et al 2016). It is also possible that powerful outflows could disrupt clumps on short timescales, implying that secular bulge growth would occur more slowly (Genel et al 2012;Förster Schreiber et al 2011).…”
Section: Introductionmentioning
confidence: 99%